Ecclesiastical Jurisdiction in Medieval East Central Europe - Balogh, Elemér (Lectures on East Central European Legal History, 2023)
To understand the legal-geographical aspect of the theme indicated in the title, it is necessary to know that medieval Europe was divided north-south, roughly between the countries north and south of the Alps. The term ‘East-Central Europe’ is a modern concept and cannot simply be traced back to the Middle Ages. The legal institutions discussed in this chapter covered, to a greater or lesser extent, the territories of present-day Bavaria, Austria, the Czech Republic, Slovakia, Slovenia,Croatia, Serbia and Poland. This region encompassed both European legal regions in terms of medieval ecclesiastical jurisdiction, since the German, Czech and Polish territories tended to be governed by the northern type of official jurisdiction, while the Hungarian kingdom’s canonical jurisdiction was of the southern type, vicarial jurisdiction. It is important to stress, however, that there are several combined elements of the two models of adjudication, and I will discuss these features in detail in this chapter. A separate sub-chapter will be devoted to ecclesiastical judicature in medieval Bohemia. The ecclesiastical judiciary focused on the dioceses, so organizational and jurisdictional rules are included in its main elements in the study. The more detailed section of the Bavarian judiciary presents all important litigants. When discussing institutions in Poland and Hungary, I also tried to highlight the parallels and differences that can be related to each other, and thus, the chapter engages in a comparative discussion of the institutions of ecclesiastical justice in Central and Eastern Europe, as promised in the title. KEYWORDS: Bavaria, Bohemia, Poland, Hungary, bishop, archbishop, consistorium, officialis, vicarius, canon law, Roman law, customary law, Tripartitum, iudex delegatus, iurisperiti, assessores, procuratores, notaries, privilegium fori, Regestrum Varadinense, doctores decretorum, mandatum transmissionale.